Pengaruh Pengawasan Melekat dan Kepuasan Kerja Terhadap Etos Kerja Pegawai Pada Badan Perencanaan dan Pembangunan Daerah Kabupaten Bogor Tahun 2007 - Ramlan Ruvendi; Devy Erisandi (STIE Binaniaga, 2007)
Work ethics means as an evaluative aspect that owns by individual or group in giving evaluation about a work activity. While close controlling is a kind of steering activity done by supervisor of each employee in improving work performance in order to achieve company’s goal effectively and efficiently. On the other hand, job satisfaction is an emotional condition that reflects someone’s feeling towards his/her job in a positive scope impact and employees attitudes on the job and all aspects they face in their work environment. The research study on the influence of close controlling on job satisfaction and work ethics shows that respondents graded the accomplishment of close controlling at Bappeda Bogor Regency averagely as good. Whilst the job satisfaction and work ethics scores at Bappeda Bogor Regency was interpreted as quite good. From Linear Regression squared analysis conducted on respondent’s data, it can be concluded that there is no or little impact between close controlling and job satisfaction at government local office, agency and district in Bogor Regency.